Speech perception performance of subjects with type I diabetes mellitus in noise - Silva, Bárbara Cristiane Sordi; Mantello, Erika Barioni; Freitas, Maria Cristina Foss; Foss, Milton César; Isaac, Myriam de Lima; Anastasio, Adriana Ribeiro Tavares (Brazilian journal of otorhinolaryngology, 2017)
Diabetes mellitus (DM) is a chronic metabolic disorder of various origins that occurs when the pancreas fails to produce insulin in sufficient quantities or when the organism fails to respond to this hormone in an efficient manner. To evaluate the speech recognition in subjects with type I diabetes mellitus (DMI) in quiet and in competitive noise. It was a descriptive, observational and cross-section study. We included 40 participants of both genders aged 18–30 years, divided into a control group (CG) of 20 healthy subjects with no complaints or auditory changes, paired for age and gender with the study group, consisting of 20 subjects with a diagnosis of DMI. First, we applied basic audiological evaluations (pure tone audiometry, speech audiometry and immittance audiometry) for all subjects; after these evaluations, we applied Sentence Recognition Threshold in Quiet (SRTQ) and Sentence Recognition Threshold in Noise (SRTN) in free field, using the List of Sentences in Portuguese test. All subjects showed normal bilateral pure tone threshold, compatible speech audiometry and “A” tympanometry curve. Group comparison revealed a statistically significant difference for SRTQ (p=0.0001), SRTN (p<0.0001) and the signal-to-noise ratio (p<0.0001). The performance of DMI subjects in SRTQ and SRTN was worse compared to the subjects without diabetes. O diabetes mellitus(DM) e um disturbio metabolico cronico de varias origens, que ocorre quando o pancreas deixa de produzir insulina em quantidade suficiente ou quando o organismo nao consegue responder a esse hormonio de maneira eficiente. Avaliar o reconhecimento de fala em individuos com diabetes mellitus tipo I (DMI) no silencio e no ruido competitivo. Estudo descritivo, observacional e transversal. Foram incluidos 40 participantes de ambos os sexos entre 18 e 30 anos, divididos em um grupo controle (GC) de 20 individuos saudaveis sem queixas ou alteraçoes auditivas, pareados por idade e sexo com o grupo de estudo, composto por 20 individuos com diagnostico de DMI. Inicialmente aplicou-se uma avaliaçao audiologica (audiometria tonal, logoaudiometria e imitanciometria) para todos os individuos; a seguir, os mesmos foram avaliados para o Limiar de Reconhecimento de Sentenças no Silencio (LRSS) e Limiar de Reconhecimento de Sentenças no Ruido (LRSR), em campo livre, por meio do teste Lista de Sentenças em Portugues. Todos os participantes apresentaram audiometria tonal dentro dos padroes de normalidade bilateralmente, logoaudiometria compativel e curva timpanometrica do tipo A. A comparaçao dos grupos revelou uma diferença estatisticamente significante para LRSS (p=0,0001), LRSR (p<0,0001) e a relaçao sinal-ruido (p<0,0001). O desempenho dos individuos com DMI para LRSS e LRSR foi pior em comparaçao com os individuos sem diabetes.